Descriptive analysis in sensory evaluation - Kemp, Sarah E.; Hort, Joanne; Hollowood, Tracey (John Wiley & Sons, 2018)
The first book in the Sensory Evaluation series is Sensory Evaluation: A Practical Handbook, published in May 2009. It focuses on the practical aspects of sensory testing, presented in a simple, 'how to' style for use by industry and academia asa step-by-step guide to carrying out a basic range of sensory tests. In-depth coverage was deliberately kept to a minimum. Subsequent books in the series cover selected topics in sensory evaluation. They are intended to give theoretical background, more complex techniques and in-depth discussion on application of sensory evaluation that were not covered in the Practical Handbook. However, they will seek to maintain the practical approach of the handbook and chapterswill include a clear case study with sufficient detail to enable practitioners to carry out the techniques presented.- Resumé vydavatel
Keywords: senzorická analýza; sensoric analysis; elektronické knihy; sborníky; electronic books; papers of several authors